2015
DOI: 10.14260/jemds/2015/122
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation Syndrome in Kashmiri Patients Scheduled for Cataract Surgery

Abstract: PURPOSE:To evaluate the prevalence of pseudo exfoliation syndrome among Kashmiri patients with age related cataract scheduled for surgery. In this study we also evaluated the prevalence of glaucoma and intraoperative complications associated with pseudo exfoliative syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In our study, 43.75% of right eyes and 46.15% of left eyes had pseudoexfoliative material deposited on both the anterior lens capsule and the pupillary margin, followed by deposition on the pupillary margin alone, then on the anterior capsule alone, and lastly on the ciliary zonules. In the study by Rashid et al ,[ 19 ] PEX deposits were seen on the anterior lens capsule and the pupillary margin in most patients (80%). In another study by Nouri-Mahdavi et al ,[ 20 ] the anterior lens capsule was observed to be the most common site of PEX deposition.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, 43.75% of right eyes and 46.15% of left eyes had pseudoexfoliative material deposited on both the anterior lens capsule and the pupillary margin, followed by deposition on the pupillary margin alone, then on the anterior capsule alone, and lastly on the ciliary zonules. In the study by Rashid et al ,[ 19 ] PEX deposits were seen on the anterior lens capsule and the pupillary margin in most patients (80%). In another study by Nouri-Mahdavi et al ,[ 20 ] the anterior lens capsule was observed to be the most common site of PEX deposition.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Rashid et al . [ 19 ] also showed nuclear cataracts to be most prevalent in the PEX group. In our study, 43.75% of right eyes and 46.15% of left eyes had pseudoexfoliative material deposited on both the anterior lens capsule and the pupillary margin, followed by deposition on the pupillary margin alone, then on the anterior capsule alone, and lastly on the ciliary zonules.…”
Section: Discussionmentioning
confidence: 99%